Young Hitler : The Making of the Führer - Ham, Paul (London Black Swan, 2017)
But there remains one aspect as yet insufficiently explored: the impact of the First World War on the man who would go on to indelibly shape the Second.Hitler fought at First Ypres and he saw something on the battlefields that eluded his fellow soldiers, something that would become the cornerstone of his later life.
Include Picture and Index
Keywords: Germany -- Heads of state -- Politics and government